Mid-luteal uterine artery Doppler indices in the prediction of pregnancy outcome in nulliparous women undergoing assisted reproduction. (8th August 2022) - Crosby, David A.; Glover, Louise E.; Downey, Paul; Mooney, Eoghan E.; McAuliffe, Fionnuala M.; O'Farrelly, Cliona; Brennan, Donal J.; Wingfield, Mary
Abstract: Traditionally, the assessment of endometrial receptivity at transvaginal ultrasound scan has been based on the thickness and the morphological appearance of the endometrium. The objective of this study was to prospectively evaluate endometrial thickness (ET), endometrial morphology and uterine artery Doppler parameters prior to assisted reproduction treatment (ART) in the prediction of pregnancy outcome. This was a prospective cohort study. ET, morphology and uterine artery Doppler (UtAD) pulsatility index (PI) and resistance index (RI) were measured in the mid-luteal stage of the menstrual cycle ultrasonographically, timed with urinary luteinizing hormone testing. A total of 50 women were included in the analysis. The clinical pregnancy rate (CPR) per embryo transfer was 42.0% ( n  = 21/50). Twenty nine women (58.0%) had an unsuccessful outcome. There were no differences in mean ± SD endometrial thickness (ET) (10.0 ± 1.8 mm vs. 10.5 ± 2.4; p  = 0.43), or endometrial morphology (100% ( n  = 21) vs 100% ( n  = 29); p  = 1.00) between the pregnant and not pregnant groups. Similarly, there were no differences in mean ± SD UtAD PI (2.17 ± 0.83 vs. 2.07 ± 0.81; p  = 0.67 or mean ± SD UtAD RI (0.84 ± 0.10 vs. 0.81 ± 0.10; p  = 0.30). Ultrasonographic endometrial assessment did not differentiate between those who would have a subsequent clinical pregnancy.